Analisis Hemming Sheet Metal dengan Variasi Jenis dan Ketebalan Material - Armunanto, Vinsentius Bram; Chrissandi, Erico S; Yosef, Herman; Hernanto, Krisna G; Herdhianto, Pujosakti; Deta, Yesaya Alfa (JMPM : Jurnal Material dan Proses Manufaktur, 2018)
The development of manufacturing industry is more rapidly, as a proof is the effeciency and speed of machining process of product manufacture. A machining process covers cutting, forming, coating, heat treatment, and casting. The bending process is included in the forming process, especially for steel plate material. The bending process uses bending tools either manual or automatic process using the program. Selection of suitable plate material will produce the optimal product, which is product free of scratch, crack or defect.The cause of bending failure can occur because the bending process parameters (bending force, methods, thickness and plate type) are not appropriate. Bending methods include v blending, u blending, r blending and hemming. Research and testing are needed to discover, analyze, and prove failure in hemming process. The result is expected to be supporting data related to product design in Work Fabrication (WF) at PT ATMI Solo.